Autism spectrum disorder: definition, global epidemiology, prevalence in Poland and worldwide, and heredity - Martyna Zakrocka; Marta Gruszka; Paulina Polańska; Maria Kubicka (Journal of Education, Health and Sport)
Introduction: The understanding of autism spectrum disorder (ASD) has evolved significantly. First mentioned in 1911, autism was described as "early childhood autism" by Leo Kanner in 1943, and a milder form, Asperger syndrome, was outlined by Hans Asperger in 1944. Expanding diagnostic criteria have led to increased recognition, with prevalence rising from 1 in 2,000 children in the 1980s to about 1 in 100 today. This growth is attributed to improved diagnostics, awareness, and healthcare access. While its exact causes remain unknown, ASD risk is influenced by genetic, environmental, prenatal, and perinatal factors, with genes like SHANK3, CHD8, and FMR1 playing key roles.